Continence outcomes of robot‐assisted radical prostatectomy in patients with adverse urinary continence risk factors. (11th May 2015) - Kumar, Anup; Samavedi, Srinivas; Bates, Anthony S.; Coelho, Rafael F.; Rocco, Bernardo; Palmer, Kenneth; Patel, Vipul R.
<x xml:space="preserve">Abstract</x> Objective To analyse the continence outcomes of robot‐assisted radical prostatectomy (RARP) in suboptimal patients that have challenging continence recovery factors such as enlarged prostates, elderly patients, higher body mass index (BMI), salvage prostatectomy, and bladder neck procedures before RARP. Patients and Methods From January 2008 through November 2012, 4 023 patients underwent RARP by a single surgeon at our institution. Retrospective analysis of prospectively collected data identified 3 362 men who had minimum of 1‐year follow‐up. This cohort of patients was stratified into six groups: Group I, aged ≥70 years (451 patients); Group II, BMI ≥35 kg/m2 (197); Group III, prior bladder neck procedures (103); Group IV, prostate weight ≥80 g (280); and Group V, salvage prostatectomy (41). Group VI consisted of patients (2 447) with none of these risk factors. Continence outcomes at follow‐up were analysed for all groups. Results The continence rate at 1 year and mean (sd) time to continence in different groups were: for patients aged ≥70 years, 85.6% and 3.2 (4.5) months; BMI of ≥35 kg/m2, 87.8% and 3.1 (4.5) months; prior bladder neck treatment, 82.4% and 3.4 (4.7) months; prostate weight of ≥80 g, 85.8% and 3.3 (4.4) months; salvage procedures, 51.3% and 6.6 (8.3) months; and in Group VI (none of the risk factors), 95.1% and 2.4 (3.2) months. The continence rate was significantly higher in group VI compared with the salvage group (group V) at the different follow‐up intervals (P < 0.001). When compared with the other groups (I–IV), the continence rate, although higher, was not statistically significant at the different intervals in group VI (no risk). The mean time to continence was significantly lower in group VI compared with the other groups (I–V; P < 0.001). Conclusions This study has shown that selected risk factors adversely affect the time to return of continence after RARP, yet aside from salvage patients, there was no statistically significant difference demonstrated between the adverse‐risk groups included. Patients undergoing salvage RP had significantly lower continence rates at the various intervals compared with the other groups. Patients with the risk factors identified should be counselled concerning expectations for achieving urinary continence.